Chronic restraint stress attenuates p53 function and promotes tumorigenesis - Feng, Zhaohui (National Academy of Sciences, 2012)
Epidemiological studies strongly suggest that chronic psychological stress promotes tumorigenesis. However, its direct link in vivo and the underlying mechanisms that cause this remain unclear. This study provides direct evidence that chronic stress promotes tumorigenesis in vivo; chronic restraint, a well-established mouse model to induce chronic stress, greatly promotes ionizing radiation (IR)-induced tumorigenesis in p53(+/−) mice. The tumor suppressor protein p53 plays a central role in tumor prevention. Loss or attenuation of p53 function contriubutes greatly to tumorigenesis. We found that chronic restraint decreases the levels and function of p53 in mice, and furthermore, promotes the growth of human xenograft tumors in a largely p53-dependent manner. Our results show that glucocorticoids elevated during chronic restraint mediate the effect of chronic restraint on p53 through the induction of serum- and glucocorticoid-induced protein kinase (SGK1), which in turn increases MDM2 activity and decreases p53 function. Taken together, this study demonstrates that chronic stress promotes tumorigenesis in mice, and the attenuation of p53 function is an important part of the underlying mechanism, which can be mediated by glucocortcoids elevated during chronic restraint.